Plant mineral concentrations related to foraging preferences of western lowland gorilla in central African forest clearings. Issue 12 (27th May 2014) - Metsio Sienne, Julia; Buchwald, Rainer; Wittemyer, George
<x xml:space="preserve">Abstract</x> In the Central African rain forest, mineral resources essential to organisms are distributed heterogeneously. Forest clearings, locally known as bais, attract numerous species presumably due to the mineral richness of these sites, though understanding of the factors drawing species to bais remains speculative. Western lowland gorillas (Gorilla g. gorilla) selectively feed on particular plant species and parts within bais, but studies of such feeding preferences have focused on one site. Here, we compared concentrations of minerals and macronutrients from plants gorillas consumed and those they did not in 16 bais to gain inference regarding drivers of resource selection within bais and bai use. The availability of gorilla feeding plants varied between surveyed bais, with some consumed species occurring only at a few bais. Regardless of bai specific species composition, significantly higher concentrations of Na, K, and Ca were found in consumed plants, and other trace minerals were more common in consumed plants. In contrast, macronutrients appeared to play no major role in feeding plant selectivity with consumed species often having lower concentrations than non‐consumed species. We found evidence for seasonal differences in Mg and Na concentrations, but the concentrations of other minerals in consumed plants were consistent across time. These findings provide insight to the drivers of bai visitation by gorillas. The high variation in species across bais may elicit use of multiple bais, but the general increased mineral composition of consumed species across bais suggests metabolic requirements may be met through consumption of a variety of species. Am. J. Primatol. 76:1115–1126, 2014. © 2014 Wiley Periodicals, Inc.